A Sec-Dependent Secretory Protein of the Huanglongbing-Associated Pathogen Suppresses Hypersensitive Cell Death in Nicotiana benthamiana - Zhang, Chao; Du, Peixiu; Yan, Hailin; Zhu, Zongcai; Wang, Xuefeng; Li, Weimin (Frontiers in Microbiology, 2020)
‘Candidatus Liberibacter asiaticus’ (CLas) is a phloem-restricted Gram-negative bacterium that is the causal agent of Citrus huanglongbing (HLB). In this study, we identified a CLas-encoded Sec-dependent secretory protein CLIBASIA_04405 that could contribute to the pathogenicity of this bacterium. The gene expression level of CLIBASIA_04405 was significantly higher in citrus than in psyllids. Transient overexpression of the mature CLIBASIA_04405 protein (m4405) in Nicotiana benthamiana leaves could suppress hypersensitive response (HR)-based cell death and H2O2 accumulation triggered by the mouse BAX and the Phytophthora infestans INF1. An alanine-substitution mutagenesis assay revealed the essential of amino acid clusters EKR45-47 and DE64-65 in cell death suppression. Challenge inoculation of the transgenic N. benthamiana expressing m4405 with Pseudomonas syringae DC3000ΔhopQ1-1 demonstrated the greatly reduced bacterial proliferation. Remarkably, transcriptome profiling and RT-qPCR analysis disclosed that the gene expression of six small heat shock proteins (sHSPs), a set of plant defense regulators, were significantly elevated in the transgenic m4405 lines compared with those in wild type N. benthamiana. In addition, the transgenic m4405 lines displayed phenotypes of dwarfism and leaf deformation. Altogether these data indicated that m4405 was a virulence factor of CLas.